(untitled) (Iraqi National Journal of Earth Science (INJES), 2026)
Air pollution is a significant problem in densely populated areas such as the university campus. This study investigates the spatial levels and distribution of air pollutants within the University of Mosul campus. A special measuring device is used with remote sensing and Geographic Information Systems (GIS) data. Ground-level monitoring data assesses major pollutants such as particulate matter (PM2.5 and PM10) and other gases. Satellite images and digital elevation models (DEMs) are processed to extract spatial distribution information of pollutant concentrations and to learn about the effects of terrain. GIS techniques analyze spatial patterns and correlations between pollutant levels and different campus features, such as transportation routes and green spaces. Ground-level monitoring stations are strategically placed throughout the campus to validate the results. The results cover the winter 2023, spring 2024, and summer 2024 periods at 16 selected locations. The results show higher concentrations of PM2.5 and PM10 in spring compared to summer and winter with values of 30.594 μg/m³ and 40.298 μg/m³ respectively. The highest concentrations are observed at the main entrances of the campus due to increased traffic. PM2.5 levels exceeded both the Iraqi limit and the WHO standard of 10 μg/m³, while PM10 concentrations exceeded the WHO limit of 20 μg/m³ but within the Iraqi limit of 50 μg/m³. This research contributes to effective environmental monitoring methodologies and highlights the importance of innovative techniques for assessing air pollution in educational institutions and urban environments.